(untitled) (Czech Journal of Multidisciplinary Innovations, 2024)
In this article, the formation of a compact state management system that meets modern requirements, the professional culture of leading personnel, the development of their spirituality, a modern leader as a person who is fully mature, mature, striving for reforms and changes, who fully possesses advanced information technologies and advanced management skills. he should be able to express himself. A modern leader should rely on the principle of justice with his personal example and high moral qualities, unite the head of the people, follow people, and be an ointment for their problems and worries. The author’s opinions were formed based on the research of the moral and ethical criteria related to the problems of training a new generation of personnel, educated in the spirit of national and universal values, capable of solving complex and large-scale tasks in the way of modernizing our country and building a modern democratic society